2022
DOI: 10.3390/ani12212943
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Farrowing Duration in Hyperprolific Sows in a Free Farrowing System under Tropical Conditions

Abstract: The ongoing selection for increased litter size has had significant impacts on sow husbandry practice. The present study investigated factors associated with farrowing duration and the proportion of sows that had prolonged farrowing in modern hyperprolific sows kept in a free farrowing system in a tropical environment. Farrowing data from 2493 Landrace x Yorkshire cross-bred sows in a commercial swine herd in Thailand were included in the study. The time of farrowing, parity number, litter size, and the birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 38 publications
7
29
0
Order By: Relevance
“…It is associated with the total number of piglets born. This is positively associated with the total number of piglets born [13,45], sow parity number [46], housing environment [40], and breeds [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with the total number of piglets born. This is positively associated with the total number of piglets born [13,45], sow parity number [46], housing environment [40], and breeds [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…This relationship can be attributed to factors associated with litter size, such as the duration of farrowing and the birth weight of piglets. In a previous study conducted by Adi et al (2022), TB was found to be positively correlated with the duration of farrowing, indicating that sows with larger litter sizes experienced longer farrowing durations compared to those with smaller litter sizes. Consequently, during prolonged farrowing in sows with higher litter sizes, more piglets may experience asphyxia and perish intrapartum, leading to an increased proportion of stillborn piglets.…”
Section: Stillbirthmentioning
confidence: 76%
“…Additionally, low body condition scores in old sows may be related to certain diseases or reproductive exhaustion, increasing the risk of stillbirth (Rangstrup-Christensen et al, 2017). Moreover, a previous study demonstrated that older sows had a longer farrowing duration compared to young ones (Adi et al, 2022). Mota-Rojas et al (2022) reported that old sows (i.e.…”
Section: Stillbirthmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 11 lists the main conclusions of some studies on the comprehensive effect of thermal–humidity environment on sows. According to Table 11, the rectal temperature, oestrus rate, ovulation rate and conception rate of sows were not significantly affected by humidity under the relative humidity of more than 80% (Adi et al, 2022; Renaudeau, Anais, & Noblet, 2003; Renaudeau, Noblet, & Dourmad, 2003; Teague et al, 1968). However, the decrease of sow feed intake and weight gain was more significantly affected by relative humidity under the high temperature of more than 27.5°C.…”
Section: Resultsmentioning
confidence: 99%